Technical efficiency of teff production in South Soddo District, Gurage Zone, Central Ethiopia Regional State, Ethiopia - Seid Mohamed Hussen; Anbes Tenaye (Discover Agriculture)
Abstract Agriculture remains the backbone of the Ethiopian economy, but productivity levels must improve to address food insecurity. In particular, enhancing the productivity and efficiency of teff cultivation could play a significant role in achieving food security. This study was conducted in the South Soddo District of the Gurage Zone in Central Ethiopia to determine the technical efficiency of smallholder teff farmers and identify factors affecting their inefficiency. The research gap identified is the lack of simultaneous estimation of production technology and the covariates of technical inefficiency, which are often addressed separately in existing studies. Using a two-stage random sampling technique, 196 sample households were selected, and a semi-structured questionnaire was employed to collect data on teff production during the 2021/22 season. The study used the Stochastic Frontier Analysis (SFA) method, specifically the Cobb–Douglas production function, to analyze the data, allowing for the distinction between random errors and inefficiency. This study found significant variations in efficiency among teff-producing farmers, with a mean technical efficiency score of 79.6%. These results suggest that teff production can be increased by 20.4% without extra inputs. Factors affecting inefficiency include age, education, land fragmentation, credit, contact with external creditors, tropical livestock, and crop rotation. The study recommends measures to improve education, establish a benevolent environment for farmers to share experiences, enhance credit service provision and enable more consistent and regular extension contacts. By addressing these factors, this study aims to contribute to a more accurate understanding of the inefficiency of teff production, ultimately supporting efforts to enhance food security in Ethiopia.